Pursuit of Well-being: Testing the Role of Empowerment, Transformational leadership, Work Engagement and Work Environment - Abdul Latif (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study aims to determine the effect of Empowerment, Transformational Leadership, Work Engagement, Work Environment. Employee well-being is an important topic in human resource management studies because it is believed to be able to produce a positive effect on company achievements. The population in this study were all employees in North Sumatra who had at least 3 years of work experience. The sample in this study was 265 employees, sampling was carried out using a saturated sampling technique or census sampling, where all members of the population were sampled. The data analysis technique used is Structural Equation Modeling (SEM) partial least square. Data processing in this study was assisted by using the Smart PLS3 application. The results showed that: Empowerment has a positive and significant effect on employee well-being.